Peranan Guru dalam Meningkatkan Karakter Disiplin Dansopan Santun Siswa di SD Tri Hita Alam ECO School Denpasar - Elmiani, N.W.S; Sulindawati, Ni Luh Gede Erni; Werang, B.R (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
Education has a crucial role in shaping the character of students, including the character of discipline and manners. This study aims to explore the role of teachers in improving the character of discipline and manners of students at SD Tri Hita Alam Eco School, Denpasar. The background of the research refers to actual problems in schools related to student discipline and manners. The research method used is a qualitative approach with case studies. Data were collected through observation, interviews, and analysis of related documents. The results showed several problems, including students arriving late, not obeying the dress code, and lack of manners towards teachers. The role of teachers in improving student character is very important. Teachers are not only teachers, but also as good guides and examples. Therefore, this study describes the role of teachers in shaping the character of discipline and manners of students. Teachers act as facilitators of learning, motivators, and enforcers of rules. The conclusion of this study shows that the role of teachers is very significant in improving the character of discipline and manners of students. It takes cooperation between teachers, schools, and parents to create an educational environment that supports the formation of student character.